Biomass energy consumption and economic growth: panel data evidence from ASEAN member countries - Ali H.S.; Adaa A.H.M.A.; Lin W.L.; Youssouf M.A. (Springer Netherlands, 2024)
The present study investigates the dynamic impact of biomass energy consumption on economic growth across nine (9) ASEAN economic union member countries for the period of 19802011. We applied heterogeneous panel cointegration techniques. The result based on Pedroni panel cointegration test shows that, variables have long-run relationship as the null hypothesis of no cointegration was rejected at 1% and 5% respectively. Kao residual cointegration test also shows the same result as null hypothesis of no cointegration is rejected at 1% level of significance. The main empirical finding based on dynamic OLS, fully modified OLS and panel OLS reveals that; there is a positive and significant relationship between biomass energy consumptions and economic growth in the region. Moreover, the result based on dynamic ordinary least square (DOLS) also shows that; capital stock and human capital have a positive and significant impact on economic growth. Same result is also obtained from fully modified OLS (FMOLS) with the exception of human capital which is insignificant on economic growth. Panel ordinary least square also reconfirmed the finding of DOLS as all the three variables significantly influences economic growth. The policy suggestion remains that, authorities in ASEAN economic union should focus more on encouraging the use of renewable sources of energy, particularly biomass source of energy considering its positive impact on enhancing economic growth with little or no environmental degradation. 2017, Springer Science+Business Media B.V., part of Springer Nature.